Protective Effects of Hypericum perforatum and Quercetin in a Rat Model of Ischemia/Reperfusion Injury of Testes - Suzen, Alev; Tekin, Leyla; Erdemli, Mehmet Erman; Erturk, Nazile; Aksungur, Zeynep; Aktas, Serdar (European Journal of Pediatric Surgery, 2018)
Purpose This study aimed to compare the protective effects of Hypericum perforatum (Hp) and quercetin, a flavonoid, against ischemia/reperfusion (I/R) injury in rat testes.Materials and Methods This study included 28 male Wistar albino rats that were divided into four groups. Except for the sham group, torsion was created by rotating both testes at an angle of 720 degrees clockwise for 2 hours. The Hp and quercetin groups received 25 mg/kg Hp and quercetin intraperitoneally 30 minutes before detorsion, respectively. Orchiectomy was performed for the measurement of markers of oxidative stress and histopathological examination.Results In the Hp and quercetin groups, malondialdehyde (MDA) and nitric oxide (NO) levels and total oxidant capacity were significantly lower, the glutathione level and total antioxidant status were significantly higher, and Johnsen's testis biopsy scores were significantly higher than in the torsion/detorsion group (p ˂ 0.001). The markers of oxidative injury were significantly lower (p ˂ 0.001) and total antioxidant status was significantly higher (p ˂ 0.001), except for glutathione (p = 0.62) in the Hp group than in the quercetin group. Johnsen's score between Hp and quercetin groups was not significantly different (p = 0.80).Conclusion Both Hp and quercetin have protective effects against I/R injury of the testes, but the protective effect of Hp was found to be stronger than that of quercetin.
Keywords: testis torsion; Hypericum perforatum; quercetin